The Existence of Religious Studies Programs at PTKIN Amid the Progressiveness of Institutional Transformation - Enghariano, Desri Ari; Rambe, Toguan (Universitas Islam Negeri Sumatera Utara, 2025)
This article documents the development and changes in institutional status transfer at PTKIN which are so massive, this shows that the position of PTKIN is so responsive to the demands of the times, so that the transformation from the form of Institute (IAIN) to University (UIN) is a necessity at PTKIN. The position of the religious studies study program which is classified as